Comparison of non-linear impedance AC response of 10 and 20 multiple quantum wells (MQWs) p-i-n Diode with DBR towards low leakage current generation of optoelectronic device - Nur Fadzilah Basri; Afishah Alias; Megat Muhammad Ikhsan Megat Hasnan; Mohammad Syahmi Nordin; Fahrettin Sarcan; Khairul Anuar Mohamad (Penerbit Akademia Baru, 2024)
This study explores the leakage current behaviour in multi-quantum well (MQW) devices using dielectric analysis. MQWs integrated with distributed Bragg reflector (DBR) show promise in enhancing optoelectronic device performance. Impedance spectroscopy and dark current-voltage measurements were conducted on 10 MQWs and 20 MQWs. The results indicate that 20 MQWs exhibit lower dielectric loss and leakage current compared to 10 MQWs. Understanding and minimizing resistive and polarization losses can improve the power efficiency and signal quality of optoelectronic devices. These findings demonstrate the importance of dielectric analysis for optimizing MQW-based optoelectronic devices.